Visual communication in Queen of Langkasuka (Film) - Hashim, Mohd Haizra; Ahmad, Abdul Mu’ati @ Zamri; Abdul, Muhammad Pauzi; Mohd Yunos, Mohd Yazid (Faculty of Communication & Media Studies, Universiti Teknologi MARA, 2017)
In the movie Queen of Langkasuka, there is a correlation between visual communication and the characters portrayed. The strength of the images is transformed into verbal aspects that make the visualization as storyteller. The weight of any film is dependent on the broad aspects of its cinematography. In this film, visual communication is elaborated by focusing on the visual aspects and the close relationship between the characters and the space composition in conveying certain messages. In the field of cinematography, the beauty of a film is relying on how its film making process shapes the characters through the visual space composition without the need to describe other characters. A film shoot requires sensitivity in the internal narrative content so that only symbolic visuals and images would communicate with the audience.